Methylation hallmarks on the histone tail as a linker of osmotic stress and gene transcription - Xiao, Mu; Wang, Jinbiao; Xu, Fang (Frontiers in Plant Science, 2022)
Plants dynamically manipulate their gene expression in acclimation to the challenging environment. Hereinto, the histone methylation tunes the gene transcription via modulation of the chromatin accessibility to transcription machinery. Osmotic stress, which is caused by water deprivation or high concentration of ions, can trigger remarkable changes in histone methylation landscape and genome-wide reprogramming of transcription. However, the dynamic regulation of genes, especially how stress-inducible genes are timely epi-regulated by histone methylation remains largely unclear. In this review, recent findings on the interaction between histone (de)methylation and osmotic stress were summarized, with emphasis on the effects on histone methylation profiles imposed by stress and how histone methylation works to optimize the performance of plants under stress.